2020
DOI: 10.1590/1678-7757-2019-0384
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gel containing bioactive glass-ceramic to minimize the pulp damage caused by dental bleaching in rats

Abstract: Experimental gel containing bioactive glass-ceramic to minimize the pulp damage caused by dental bleaching in rats Objectives: This study evaluated if the use of a bioactive glass-ceramicbased gel, named Biosilicate (BS), before, after or mixed with bleaching gel, could influence the inflammation of the dental pulp tissue of rats' molars undergoing dental bleaching with hydrogen peroxide (H 2 O 2). Methodology: The upper molars of Wistar rats (Rattus norvegicus, albinus) were divided into Ble: bleached (35% H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…In animal studies (19 studies), 18 of them assessed the inflammatory response, and all demonstrated significant inflammation in the most superficial regions of coronal pulp, often accompanied by necrotic areas. This was particularly evident after bleaching with 35% or 38% HP and during the initial periods (Barbosa et al., 2019; Benetti et al., 2017; Benetti, Briso, et al., 2018; Benetti, Briso, Carminatti, et al., 2019; Benetti, Briso, de Araújo Lopes, et al., 2019; Benetti, Gomes‐Filho, et al., 2018; Carminatti et al., 2020; Cintra et al., 2013, 2017; Cintra, Benetti, Ferreira, Gomes‐Filho, et al., 2016; da Silva et al., 2020; Ferreira et al., 2018; Gallinari et al., 2019; Lima et al., 2016; Louzada et al., 2019; Seale et al., 1981; Silva‐Costa et al., 2018; Terayama et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In animal studies (19 studies), 18 of them assessed the inflammatory response, and all demonstrated significant inflammation in the most superficial regions of coronal pulp, often accompanied by necrotic areas. This was particularly evident after bleaching with 35% or 38% HP and during the initial periods (Barbosa et al., 2019; Benetti et al., 2017; Benetti, Briso, et al., 2018; Benetti, Briso, Carminatti, et al., 2019; Benetti, Briso, de Araújo Lopes, et al., 2019; Benetti, Gomes‐Filho, et al., 2018; Carminatti et al., 2020; Cintra et al., 2013, 2017; Cintra, Benetti, Ferreira, Gomes‐Filho, et al., 2016; da Silva et al., 2020; Ferreira et al., 2018; Gallinari et al., 2019; Lima et al., 2016; Louzada et al., 2019; Seale et al., 1981; Silva‐Costa et al., 2018; Terayama et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies are described in Table 1. Among the 19 studies that used experimental rat models, 16 of them used upper molars (Barbosa et al., 2019; Benetti et al., 2017; Benetti, Briso, et al., 2018; Benetti, Briso, Carminatti, et al., 2019; Benetti, Briso, de Araújo Lopes, et al., 2019; Benetti, Gomes‐Filho, et al., 2018; Carminatti et al., 2020; Cintra et al., 2013, 2017; Cintra, Benetti, Ferreira, Gomes‐Filho, et al., 2016; Cintra, Benetti, Ferreira, Rahal, et al., 2016; da Silva et al., 2020; Ferreira et al., 2018; Gallinari et al., 2019; Louzada et al., 2019; Terayama et al., 2020). Twelve studies were conducted using human teeth, including molars ( n = 2), premolars ( n = 8) and incisors ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] 45S5 BG increases the pH of the environment to an alkaline level with the dissolution of the ions in its structure at the time in the biological fluid. [25,26] For this reason, a biomaterial with stronger antibacterial activity has been designed by using CH and 45S5 BG together. CH can interact with the tissues in the mouth and release chemicals for a longer duration.…”
mentioning
confidence: 99%